2018
DOI: 10.1016/j.jpowsour.2018.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Alginic acid-derived mesoporous carbonaceous materials (Starbon®) as negative electrodes for lithium ion batteries: Importance of porosity and electronic conductivity

Abstract: Alginic acid-derived mesoporous carbonaceous materials (Starbon¨ A800 series) were investigated as negative electrodes for lithium ion batteries. To this extent, a set of mesoporous carbons with different pore volume and electronic conductivity was tested. The best electrochemical performance was obtained for A800 with High Pore Volume (A800HPV), which displays both the highest pore volume (0.9 cm 3 g-1) and the highest electronic conductivity (84 S m-1) of the tested materials. When compared to a commercial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…TEM-EDX mapping (Figure 4d-f) revealed that both carbon and TiO 2 particles were homogeneously dispersed with no segregation. In the case of A600 ( Figure S5),T EM confirmed that the mesoporosity arose from the entanglement of bundles of AA chains (with a [58] present in the cryogel and maintained during carbonization. The Raman spectra of the samples before thermalt reatment did not present any signals that were clear or strong enough to be interpreted.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…TEM-EDX mapping (Figure 4d-f) revealed that both carbon and TiO 2 particles were homogeneously dispersed with no segregation. In the case of A600 ( Figure S5),T EM confirmed that the mesoporosity arose from the entanglement of bundles of AA chains (with a [58] present in the cryogel and maintained during carbonization. The Raman spectra of the samples before thermalt reatment did not present any signals that were clear or strong enough to be interpreted.…”
Section: Resultsmentioning
confidence: 80%
“…A small cathodic peak at 0.7 V, recorded only during the first cycle, was attributed to the decomposition of electrolyte on the surface of the electrode. In case of mesoporous carbonaceous material A600 (Figure c), the two cathodic peaks at 1.4 and 0.7 V during the first cycle were probably owing to irreversible reactions such as the reaction of lithium with oxygenated surface groups in A600 (1.4 V) and the decomposition of electrolyte (0.7 V), resulting in the formation of the SEI . These two peaks were not observed during the subsequent cycles, leaving only a peak at 0.1 V associated with the reversible insertion of lithium in amorphous carbon.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Interconnected and hierarchical pore structures were shown to improve the diffusion of lithium ions, while high specific surface areas promote efficient charge-transfer processes at the electrode-electrolyte interface. [2,3] Note that such high surface area can also severely impact the efficiency of the first cycle. Different approaches and precursors were developed for the synthesis of advanced porous carbons with high specific surface areas and pore volumes.…”
Section: Introductionmentioning
confidence: 99%